The effect of science process skills of students argumentation skills - Darmaji Darmaji; Astalini Astalini; Dwi Agus Kurniawan; Elza Triani (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2022)
This study aims to compare students' learning skills in each class and students' argumentative abilities in each class and to determine the effect of students' science process skills on students' argumentation abilities. This type of research uses the mixed method with an explanatory design. The samples of this study were 70 students of class 11 science, with the sampling technique of simple random sampling. The results of data analysis using parametric statistics t-test (2-tailed) obtained sig. value 0.034 0.05, so it can be said that the students' argumentative abilities in XI A and IPA B are different, and for the variable science process skills, the sig. is 0.043 0.05, so each class's science process skills are different. The results of the regression test obtained the results of the sig value of 0.025 in class XI A, and class XI B obtained a sig value of 0.030, where the value of sig 0.05 which means that science process skills affect the students' argumentation skills. The study confirms that the improvement of scientific skills will make student better at conveying arguments.